Tanggung Jawab Pelaku Usaha Batu Bata Terhadap Perbaikan Lingkungan Hidup Perspektif Fatwa MUI No. 22 Tahun 2011 (Studi Desa Jambur Padang Matinggi Kabupaten Mandailing Natal) - Indah, Khofifah; Permata, Cahaya (Universitas Ekasakti, 2023)
The majority of residents of Jambur Padang Matinggi Village are brick-making businesses, which are one of the main building materials. Making bricks requires clay taken from hilly land by digging. Excessive digging of clay certainly has a detrimental impact on the environment, so the aim of this research is to determine the impact and damage to the environment caused by the brick business, and how to be responsible for it. environmental improvements due to land excavation. This type of research is empirical juridical with a living case studies approach and a conceptual approach. Data was collected using interviews, observation and document study methods. Then the data is processed and analyzed using qualitative methods. The results of this research show that land excavation in Jambur Padang Matinggi Village has caused environmental damage, such as damage to the quality and quantity of soil, the number of excavated holes, decreased water quality and air pollution, which can result in natural disasters, especially floods and landslides. Based on the MUI Fatwa, business actors are obliged to be responsible for carrying out environmental improvements at the site of excavated land.